Peran Layanan Bimbingan Konseling Terhadap Kesadaran Ibadah Shalat Siswa Melalui Pembelajaran Pendidikan Agama Islam - Hidayani Syam; Anisa Wahyuni; Halimah Tusa’diah; Andre Saputra (Kampus Akademik Publiser, 2025)
Counseling guidance services play an important role in students' awareness of praying in Islamic religious education, there are many impacts that influence students' religious awareness, especially in carrying out prayers. In this case, the influence of counseling guidance services is very useful in helping students overcome personal, academic and social problems. as well as providing direction in developing students' religiosity, especially in carrying out prayers. The research method used is a qualitative approach with a case study design, which involves analyzing documents in the form of articles to understand the influence of counseling guidance on awareness of prayer in the Islamic religion. The data collected was in the form of articles containing discussion of the influence of counseling on awareness of prayer in the Islamic religion. The research results obtained from the influence of counseling guidance on awareness of praying in Islamic religious education are that it has a positive impact on awareness of praying in Islamic religion, increasing students' development in carrying out prayers with counseling guidance services, can help students set a better mindset in worship and in activities and be more diligent in worship. This research concludes that the influence of counseling guidance services can play an important role in increasing students' awareness of worship in performing prayers and can integrate religious values ​​in daily life.